The Effect of Number of Bays and Story on the Required Time Gap Between Mainshock and Aftershock Earthquake for Time History Dynamic Analysis - Zacharias, Hendry David (Jurnal Teknik Sipil, 2025)
Seismic sequences cause cumulative structural damage; therefore, aftershocks must be considered in design. A key factor in time history analysis with seismic sequences is the time gap (TR) between the mainshock and aftershocks, during which acceleration is zero. TR is critical, as long earthquake durations can lead to high analysis time and cost. This study analyzed 16 structural models with varying numbers of bays and stories but identical plan areas, using seven records from the 1994 Northridge earthquake. At zero acceleration, a TR value of 60 seconds is added and will be increased to 120 seconds, if the acceleration and speed values ​​of the roof structure do not reach values ​​very close to zero (AR0 and VR0). Results show that TR increases almost linearly with the structural period (TS). Thus, increasing the number of bays reduces TR if TS decreases, while increasing the number of stories raises TR if TS increases. However, earthquakes with longer predominant periods result in smaller TR values.